SAND IRON MORTAR WITH ADDITION OF LEAD OXIDE Pb3O4 VARIATION AS RADIATION SHIELDING OF X AND GAMMA RAYS - Yasinta Yerry Permana Sari (Journal of the Civil Engineering Forum, 2013)
To find out the ideal radiation shielding material from civil engineering and radiation aspect especially in the medical sector, in this research made sand iron mortar was made with mix proportion of 1:4 with addition variation of lead oxide Pb3O4 that are 0% (M1), 20% (M2), 30% (M3), and 40% (M4) of loose volume of sand iron and also Viscocrete-10 addition 0.6% of cement weight. Water cement ratio used for M1, M2, M3, and M4 are 0.4, 0.41, 0.44, and 0.48 respectively. Sand iron and lead oxide Pb3O4 as fine aggregate are tested to obtain its density and unit weight as a basis to calculate the mix design. The specimens of each variable of mortar are tested on its physical and mechanical properties, namely weight per m3, compressive strength, tensile strength, and water absorption with the number of specimens are 3 (three) of each variable of mortar. After that, the specimens are tested with Gamma radiation with energy 1170 keV, 1330 keV (Cobalt 60), 662 keV (Cesium 137), and 323 keV (Cr 51) and X Ray radiation with energy 70 kV and 90. The specimens are block shaped size 10 cm x 10 cm with thickness variation of 1 cm up to 12 cm.The result shows that the density of sand iron and lead oxide Pb3O4 are 3,8259 and 8,4693 respectively and the unit weights are 1,965 gr/cm3 and 2,535 gr/cm3 respectively. Weight per m3 of mortar was increased caused by the increasing of lead oxide Pb3O4 on mortar. The compressive strength significantly increased starting on M2 (37,328 MPa) from M1 (7,594 MPa) and a bit decreased on M3 and M4, i.e. 32,188 Mpa and 30,144 Mpa respectively caused by the increase of water cement ratio. The value of water absorption was decreased as an effect of lead oxide Pb3O4 addition. From the result of Gamma radiation test, it shows that the higher the density, the higher the attenuation coefficient of the material and if the energy increases, the attenuation coefficient of the material decreases except at the energy above 1200 keV where the attenuation coefficient increases back as a result of a pair production phenomenon. The attenuation coefficient values of M1, M2, M3, and M4 are 0.102 cm-1, 0.145 cm-1, 0.152 cm-1, and 0.184 cm-1 respectively for energy 1330 keV; 0.060 cm-1, 0.104 cm-1, 0.120 cm-1, and 0.155 cm-1 respectively for energy 1170 keV; 0.157 cm-1, 0.212 cm-1, 0.242 cm-1, and 0.284 cm-1, respectively for energy 662 keV, and 0.202 cm-1, 0.309 cm-1, 0.330 cm-1, and 0.426 cm-1 respectively for energy 323 keV. The different result shows rom X ray radiation test whereas occurred inaccurate data as a result of scattering caused by wide beam owned by X ray so that the result cannot be compared with the result of Gamma radiation test. So, the results of X ray radiation test which can be used are the X ray photo of mortars that shows the homogeneity of each variable of mortar. From the effectiveness aspect as a radiation shielding, mortar M4 is the most effective because it has the biggest attenuation coefficient value.